QUALITATIVE CHANGES IN JAPAN’S POLICY IN THE FIELD OF MILITARY SECURITY IN 2013 - D. V. Streltsov (MGIMO University Press, 2013)
The article deals with the qualitative changes that have taken place in the course of Japan in the field of military security in December 2012 after the rise of the second Abe Cabinet. These changes include tightening of the policy towards China, stronger defense policy coordination with the countries concerned with the growth of Beijing's military ambitions, as well as the revision of the basic strategy of defense capacity-building.A special place in Tokyo’s new policy was taken by the moves aimed at revising the Constitution. Constitutional reform is seen in Tokyo as a sort of milestone marking the end of the postwar Japanese history when Japan held the position of the "junior partner" of the United States. However, even within the framework of the Constitution the Abe Cabinet strives to achieve a full legitimization of the self-defense forces’ missions outside Japan, formally to maintain peace and security, but essentially to meet the requirements of the Security Treaty.The author concludes that the future policy of Japan in the field of military security will be to a large extent determined by the situation around the territorial dispute with China. Apparently, the Chinese ships’ patrolling of the areas around the Senkaku will become a routine practice, and Japan will have to if you do not accept, but at least to get used to a permanent Chinese presence in the disputed waters. Thus, the question is how to establish bilateral mechanisms of preventing escalation of tension to the stage of an armed conflict.Key words: Japan, the Constitution, the National Security Council, the restrictions on the export of arms, the right of collective self-defense, territorial dispute, the UN Convention on the law of the sea, the Shangri-La dialogue.